The broadcasting demand for the Spanish national soccer team - Artero, I.; Bandrés, E. (Journal of Sports Economics, 2018)
This article analyzes the broadcasting demand in Spain for the Spanish national soccer team. The variability in audience figures suggests supplementing the ordinary least squares estimation with quantile regressions to understand the effect of the explanatory variables across the conditioned distribution of television audiences. The results show that variables associated with the sporting relevance of each game and the reputation of the opponent are significant, while consumer habits have little influence and uncertainty of outcome is not significant. The different degrees of influence of the variables across all quantiles confirm the heterogeneous nature of demand.